Diversification of spider silk properties in an adaptive radiation of Hawaiian orb-weaving spiders - Alicea-Serrano, Angela M.; Jain, Dharamdeep; Dhinojwala, Ali; Blackledge, Todd A. (Frontiers in Arachnid Science, 2024)
The design of biological structures and the materials composing those structures are intimately connected to performance in biological systems. Spider webs present an excellent example of how design and materials interact during their function in capturing prey. Major shifts in how spider webs capture prey have occurred due to evolutionary changes of both web architecture and silk properties. However, these shifts are mostly described for long timescales deep within the spider tree of life. Hawaiian Tetragnatha present an opportunity to ask if such shifts can occur at much shorter timescales because web design diverges significantly among closely related species on the same island, but also converges with more distant relatives on other islands. Here, we provide an initial test of whether or not silk properties diversified during the recent adaptive radiation of Hawaiian Tetragnatha. We obtained radial and capture spiral silk from orb webs for spiders from two islands and tested their tensile and adhesive properties. We also used solution-state NMR to compare composition of low molecular weight compounds in the glue because of their influence on capture spiral stickiness. Results showed differences in the stiffness of radial silk among four populations of Hawaiian Tetragnatha, while extensibility remained unchanged. Although not statistically different, radial strength and toughness varied two-fold among species. Stickiness varied three-fold among the four populations of orb weavers.No conspicuous qualitative differences in low molecular weight compound composition of aggregate glue were found, suggesting that differences in capture spiral stickiness were due to the amount or arrangement of glue droplets on threads. While our sampling is modest, our data provide the first evidence that silk properties can evolve measurably over the relatively short timescales of adaptive radiation of Hawaiian Tetragnatha spiders.